Validity of a procedure to identify patients with chronic idiopathic thrombocytopenic purpura in the Danish National Registry of Patients - Katrine Edith Klith Heden; Annette Østergaard Jensen; Dora Körmendiné Farkas; Mette Nørgaard (Clinical Epidemiology, 2009)
Katrine Edith Klith Heden, Annette Østergaard Jensen, Dora Körmendiné Farkas, Mette NørgaardDepartment of Clinical Epidemiology, Aarhus University Hospital, DenmarkBackground: Administrative data may be useful for epidemiological studies of chronic idiopathic thrombocytopenic purpura (ITP). However, the quality of the recorded diagnoses needs evaluation.Aim: We evaluated the validity in predicting chronic ITP of the International Classifi cation of Diseases (ICD)-10 diagnoses of ITP in the Danish National Registry of Patients (NRP).Methods: We used the NRP to identify patients with ITP, according to code D69.3, from January 1, 1996 to December 31, 2007. We defined chronic ITP as lasting longer than 6 months by including only patients with 2 or more hospital ITP diagnoses over longer than 6 months. We confirmed diagnoses by evaluating each candidate chronic ITP patient’s medical chart and estimating the positive predictive value (PPV) and 95% confidence interval (CI) of the recorded NRP diagnostic code.Results: We identified 513 patients with chronic ITP in the NRP. We were able to retrieve the charts of 439. After evaluation of the charts, 410 patients were deemed to have a valid diagnosis of chronic ITP, yielding a PPV of 0.93 (95% CI: 0.91–0.96).Conclusion: The validity of this procedure to identify chronic ITP patients was high. The NRP is valid for epidemiological studies of patients with chronic ITP.Keywords: validity, idiopathic thrombocytopenic purpura, National Registry of Patients